Construction of Fisherfolk Community Social Network in Mataram City, West Nusa Tenggara - W., Winengan (UI Scholars Hub, 2021)
This article intends to describe the construction of social networks as a tradition of socio-economic solidarity that is preserved in the life of traditional fishing communities. This article begins with the argument that the formation of social networks is a strategy for traditional fisherfolk to use social relations to survive in the face of income uncertainty. This paper shows that the existence of traditional fisherfolk social networks in Ampenan, Mataram City is the ultimate solution for them in dealing with the dynamics of economic life, with f luctuations in their limited income. The formation of social networks is based on the interests and feelings and is maintained in a stable manner, because it takes place continuously. However, the existence of this social network is only able to become a temporary alternative solution, so that it has not been able to permanently free the traditional fishing community from the pressures of their families’ daily economic needs